An algorithm to estimate muscle force from joint angle using SIMULINK - Son, J.; Hwang, S.; Kim, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to compare the muscle length and muscle force from developed model and commercial software. Basically a Hill-type muscle model consists of springs and damper, and thus muscle force was changed by muscle length. Because of this reason, the researchers needed to know the changes in muscle length and developed algorithm to estimate muscle length from joint angle (angle-to-length). Also, we implemented muscle model (length-to-force) based on the model that F. E. Zajac modified the Hill-type muscle model. Muscle lengths and muscle forces show significantly good correlation in ankle muscles in results from two methods. This indicates that angleto-force can be adapted to developed a tool determining muscle forces in real-time.